2023
DOI: 10.1037/neu0000832
|View full text |Cite
|
Sign up to set email alerts
|

Construct identification in the neuropsychological battery: What are we measuring?

Abstract: Objective: Major obstacles to data harmonization in neuropsychology include lack of consensus about what constructs and tests are most important and invariant across healthy and clinical populations. This study addressed these challenges using data from the National Neuropsychology Network (NNN). Method: Data were obtained from 5,000 NNN participants and Pearson standardization samples. Analyses included variables from four instruments: Wechsler Adult Intelligence Scale, 4th Edition (WAIS-IV); Wechsler Memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…It remains unclear how much time is necessary to arrive at accurate estimates of true scores for these subtests; this could be a valuable topic for future research. Our prior confirmatory factor analyses further showed that WAIS-IV index scores, including the Perceptual Reasoning Index to which MR contributes, might be well estimated with only 2 subtests per index (Bilder et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It remains unclear how much time is necessary to arrive at accurate estimates of true scores for these subtests; this could be a valuable topic for future research. Our prior confirmatory factor analyses further showed that WAIS-IV index scores, including the Perceptual Reasoning Index to which MR contributes, might be well estimated with only 2 subtests per index (Bilder et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Factor analytic work has shown that the Matrix Reasoning subtest loads together with other measures (Visual Puzzles, Block Design) to form the WAIS-IV Perceptual Reasoning Index (Wechsler et al, 2008;Wechsler, 2008a). We recently used confirmatory factor analysis to demonstrate that the WAIS-IV factor structure shows strong measurement invariance across a heterogeneous patient group from the NNN and the original healthy standardization sample (Bilder et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was heterogeneity in the cognitive tests used across studies. This is likely due to the fact that, in the neuropsychological literature, a large variety of cognitive tests are available and there is no consensus on whether some are more robust than others [ 81 , 91 , 164 , 165 ]. In order to ensure better comparability between studies, it is thus important that research groups employ shared protocols for cognitive assessment.…”
Section: Discussionmentioning
confidence: 99%
“…• In an effort to identify evidence-based and optimally efficient measurements of neuropsychological constructs that are valid across healthy and clinical populations, Bilder et al (2022) employ advanced psychometric methods utilized in the National Neuropsychology Network to identify the most salient cognitive constructs from flexible test batteries that are invariant across heterogenous groups.…”
Section: Special Issue Articlesmentioning
confidence: 99%